The Roles of Race, Ethnicity, Gender, and Mental Health in Predicting Truancy Recidivism - Hong, Judy H. (Criminal justice and behavior, 2020)
This study aims to (a) describe demographic and mental health (MH) differences between truant juvenile justice-involved youth (JJY) and nontruant JJY; (b) classify MH needs of truant JJY; and (c) investigate if the interactions between race, ethnicity, gender, and MH needs predict truancy recidivism. Participants were 10,603 truant JJY (55.4% male; non-Hispanic White, 46.8%; 16.2% with a history of pretrial detention). Of these participants, 2,167 with MH data were included in latent profile analyses and recidivism analyses. Hispanic youth and female youth were more likely to be truant. Non-Hispanic White JJY had a higher likelihood of a repeated truancy charge. Four MH classes emerged: elevated Alcohol/Drug Use (7.9%), elevated Angry-Irritable and Depressed-Anxious symptoms (19.5%), elevated Suicide Ideation (7.1%), and low MH needs (65.5%). Race, ethnicity, gender, and MH needs are informative as potential factors contributing to truancy. These factors should be examined in future studies that compare truant with nontruant non-JJY.